Geochemical Evidence from Major and Trace Elements in Geothermal Waters of Empat Lawang, Southern Sumatra: Clues to Mineralization and Hydrothermal Sources - Umam, Rofiqul; Suharno, Suharno; Junaidi, Rahmad (Leuser Journal of Environmental Studies, 2025)
This study explores the major and trace element geochemistry of geothermal waters from Empat Lawang, Southern Sumatra, Indonesia, to assess hydrothermal origins and mineral prospecting potential. Five water samples were analyzed using ternary plots, ion correlation diagrams, and geothermometric equations. A strong Na–Cl correlation (R2 = 0.9694) suggests evaporite dissolution or mixing with connate water, while the Ca–SO4 relationship (R2 = 0.9555) indicates gypsum or anhydrite dissolution. The Ca + Mg vs. HCO3 pattern reflects carbonate and silicate weathering influenced by lithological variability. Diagnostic ion plots reveal active ion exchange and halite dissolution across sample sites. Reservoir temperatures estimated using Giggenbach and Fournier Truesdell equations range from 190°C to 404°C, with an outlier of 1593.75°C in PN3, likely due to fluid disequilibrium. Depths span 4.22 to 16.39 km, indicating deep-seated hydrothermal systems with intense fluid–rock interaction. The Cl/Li vs. B plot identifies hydrothermal signatures, with most samples below the Cl/Li < 1000 threshold and elevated boron levels, suggesting active leaching and mineral transport. These findings highlight the potential for borate and metal mineralization. By integrating classical geochemical approaches with modern trace element indicators, this study provides a novel framework for geothermal exploration in Indonesia’s volcanic regions. These findings suggest potential for borate and metal mineralization and offer a geochemical framework for geothermal exploration in Indonesia’s volcanic regions.